Transmission of Monetary Policy in Canada: Does the Money Multiplier Exist? - Gianopoulos, Demetri (Université d'Ottawa | University of Ottawa, 2013)
This paper examines whether a money multiplier mechanism or narrow bank lending channel is operative in the monetary transmission of the Canadian banking system for the period 1968-2007. By employing Structural Vector Auto-Regression (SVAR) models, proposed by Bernanke & Blinder (1992) and Carpenter & Demiralp (2011), this paper concludes that the evidence for Canada indicates that the money multiplier is not the main transmission mechanism in Canada. This paper compares the Canadian results with an identical examination of the US banking system for the same time period. The evidence for the overall sample period indicates that the money multiplier mechanism has less of an impact in Canada than for the US. For both Canada and the US there is a break in the response of total loans and reservable deposits starting in the late 1980’s and early 1990’s. This break in the data is likely caused by institutional, legislative and regulatory changes occurring in the respective banking and financial systems. In addition, the results also indicate significant differences between Canada and the US when the overall sample period is broken down into the subsamples 1968-1989 and 1990-2007. The results for the US, consistent with Carpenter and Demiralp (2011), suggest that the money multiplier was an operative monetary transmission mechanism in the 1968-1989 period but not in the 1990-2007 subsample. The results for the Canadian data, for the same subsample periods, are exactly the opposite. These puzzling results call for a more detailed analysis of the reasons explaining these differences between Canada and the US. A more formal analysis evaluating the role of different factors in the structure of the banking sectors and regulatory requirements in the two countries would further our understanding of the money multiplier mechanism.